The Development of e-PSM System for Undergraduate Students of Faculty Food Science and Nutrition (FSMP), University Malaysia Sabah(UMS) - Fang, Shi Yun; Rozanawati Darman (Applied Information Technology And Computer Science, 2022)
The e-PSM system is a web-based system and specially developed for year 3 students of the Faculty of Food Science and Nutrition (FSMP) in University Malaysia Sabah. Project users are students, supervisors, and coordinators. This project aims to assist year 3 students while starting and creating final year projects. Students will be more comfortable and systematic to make weekly activity reports after discussion with the supervisor. The coordinator can easily gather information of all Year 3 students and supervisors. The project is developed based on the Prototype model where improvements are made from time to time. The software used to build the e-PSM system is Brackets, Notepad, and XAMPP. Additionally, phpMyAdmin is used for system databases. There are four modules in the e-PSM System, namely the login module, user registration module, activity report generator module, and student group assignment to the supervisor module. Based on the testing by test plan, it is shown that the actual output is the same as the expected output. For the user acceptance testing, most of the respondents felt strongly satisfied and satisfied with the system